Synchronization and Changes in International Inflation Uncertainty - Steffen Henzel; Elisabeth Wieland (Center for Economic Studies and ifo Institute (CESifo), 2013)
We investigate the international linkages of inflation uncertainty in the G7. In a first step, we document that inflation uncertainty in the G7 is intertwined. Moreover, the degree of synchronization has increased during the recent two decades. Second, based on a Factor-Structural Vector Autoregression (FSVAR) model, we provide evidence of a common international shock that drives national inflation uncertainty and which is closely related to oil and commodity price uncertainty. Third, we document that the size of shocks to inflation uncertainty has declined over time paralleling the process of inflation stabilization. Fourth, we analyze whether this decline can be explained by “good policy” or by “good luck”. It appears that domestic shocks translate less extensively into the individual economies. We interpret this finding in favor of the “good policy” hypothesis. Finally, we document that the relative importance of international shocks has increased which explains the higher degree of synchronization in inflation uncertainty among the G7.
Keywords: C38; E31; E32; 330; inflation uncertainty; Factor-Structural VAR; stochastic volatility